1990
DOI: 10.1055/s-2007-1004977
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Use of Tolazamide in Newly-Diagnosed Diabetic Children

Abstract: Recent data suggests that one of the major actions of sulfonylureas is to potentiate the anabolic cellular effects of insulin. This is the first study to examine the use of sulfonylureas as adjunctive therapy in newly-diagnosed type I diabetic children. A random, prospective, double blind study over 15 months, stratified by age at diagnosis, was conducted. The treatment group (n = 13) received daily oral weight-adjusted tolazamide whereas the control group (n = 11) received placebo. Monthly comparison of the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…For sulphonylurea adjunctive therapy, there were three studies with 75 participants 40–42 . Only one of the studies 40 reported on insulin dose, but baseline imbalances between groups preclude meaningful interpretation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For sulphonylurea adjunctive therapy, there were three studies with 75 participants 40–42 . Only one of the studies 40 reported on insulin dose, but baseline imbalances between groups preclude meaningful interpretation.…”
Section: Resultsmentioning
confidence: 99%
“…For sulphonylurea adjunctive therapy, there were three studies with 75 participants 40–42 . Only one of the studies 40 reported on insulin dose, but baseline imbalances between groups preclude meaningful interpretation. Meta ‐analysis of two studies 40,42 indicated there was evidence of a difference between adjunctive treatment with sulphonylurea and control with regard to effect on HbA 1c up to 12 months of follow‐up (−5.7 mmol/mol (−0.52%) 95% CI: −16.4 (−1.5%) to 4.9 (0.45%); p = 0.29).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation